2005
DOI: 10.1590/s1676-06032005000300006
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians of an open cerrado fragment in southeastern Brazil

Abstract: The Cerrado encompasses ca. 2 million km 2 in Brazil. Most Cerrado areas have been greatly disturbed in the past decades. Only 20% of this biome remain undisturbed, and only 1.2% is protected. Knowledge on the biology and diversity of Cerrado amphibian assemblages is still incipient. Here we present natural history information (habitat use and reproductive activity) of 28 species of frogs from the Estação Ecológica de Itirapina (EEI), and compare the composition of this assemblage with those of other Cerrado a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
55
1
92

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(159 citation statements)
references
References 19 publications
11
55
1
92
Order By: Relevance
“…This fact becomes even more worrying considering that northeastern region of the São Paulo state has one of highest deforestation and fragmentation rates in the state (Rodrigues et al 2008 Table 1). The large number of anuran species associated with water bodies in Cerrado and semideciduous forest fragments during the reproductive period has been demonstrated in other studies (Brasileiro et al 2005, Bertoluci et al 2007, Araujo et al 2009, Araujo & Almeida-Santos 2011, Valdujo et al 2012). According to Santos et al (2009), anuran communities from Semideciduous Atlantic Forest and Cerrado environments are more similar to each other than they are to those of Ombrophilous Forest environments.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…This fact becomes even more worrying considering that northeastern region of the São Paulo state has one of highest deforestation and fragmentation rates in the state (Rodrigues et al 2008 Table 1). The large number of anuran species associated with water bodies in Cerrado and semideciduous forest fragments during the reproductive period has been demonstrated in other studies (Brasileiro et al 2005, Bertoluci et al 2007, Araujo et al 2009, Araujo & Almeida-Santos 2011, Valdujo et al 2012). According to Santos et al (2009), anuran communities from Semideciduous Atlantic Forest and Cerrado environments are more similar to each other than they are to those of Ombrophilous Forest environments.…”
Section: Resultssupporting
confidence: 61%
“…Although several authors have shown that the anuran species of the Cerrado and semideciduous forest fragments are mostly associated with open areas (e.g., Brasileiro et al 2005, Araujo et al 2009, Araujo & Almeida-Santos 2011, Valdujo et al 2012), here we recorded 50% of species (12 species) occurring in forest areas. It should be emphasized that forests are important mesic environments, being used by adults and juveniles as refuge sites and for foraging, hibernation, and migration, especially during dry periods (Da Silva & Rossa-Feres 2007).…”
Section: Resultscontrasting
confidence: 57%
“…Essas espécies habitam formações vegetais originalmente abertas (cf. Brasileiro et al 2005) e expandem as suas distribuições geográficas com os desmatamentos e conseqüente alteração da paisagem natural (Haddad 1998). Quando os ambientes alterados propiciam a estas espécies colonizadoras alimento abundante, abrigos e locais adequados para a reprodução, podem favorecer a permanência de suas populações (e.g., Meshaka 1996, Henderson & Powell 2001.…”
Section: Discussionunclassified
“…In Roraima, reproductive biology and mating behavior were described (MARTINS, 1988). In the southeast of Brazil, BRASILEIRO et al (2005) and OLIVEIRA-FILHO et al (2005) also studied seasonality reproductive patterns. In Pantanal of Mato Grosso do Sul, the reproduction occurs during rainy season (AVILA & FERREIRA, 2004) and the reproductive biology was studied by PRADO & HADDAD (2003, 2005.…”
Section: Leptodactylus Fuscusmentioning
confidence: 99%